Synthesis and Characterisation of Dihydroxystearic Acid-Estolides from Palm-Based Dihydroxystearic Acid - Nor Azizan, Aminah (2006)
Estolide is a polyfunctional oligomer that contains ester linkages on the alkyl backbone of the molecule, which is formed by the esterification reaction between fatty acids. These ester linkages are more resistant to hydrolysis than those of triglyceride. The unique structure of the estolide makes it has superior physical properties if compared to the mineral and vegetable oil in certain applications. Estolides can be potentially used in a variety of applications, such as surfactants, ingredient or additive in cosmetic and inks formulations.